Efficacy and safety profiles of programmed cell death-1/programmed cell death ligand-1 inhibitors in the treatment of triple-negative breast cancer: a comprehensive systematic review - Gilbert Lazarus; Jessica Audrey; Anthony William Brian Iskandar (Frontiers Media S.A., 2019)
Triple-negative breast cancer (TNBC) is associated with worse prognosis, with limited treatment regiments available and higher mortality rate. Immune checkpoint inhibitors targeting programmed cell death-1 (PD-1) or programmed cell death-ligand 1 (PD-L1) showed great potentials in treating malignancies and may serve as potential therapies for TNBC. This systematic review aims to evaluate the efficacy and safety profiles of PD-1/PD-L1 inhibitors in the treatment of TNBC. Literature search was performed via PubMed, EBSCOhost, Scopus, and CENTRAL databases, selecting studies which evaluated the use of anti-PD-1/PD-L1 for TNBC from inception until February 2019. Risk of bias was assessed by the Newcastle-Ottawa Scale (NOS). Overall, 7 studies evaluating outcomes of 1395 patients with TNBC were included in this systematic review. Anti-PD-1/PD-L1 showed significant antitumor effect, proven by their promising response (objective response rate (ORR), 18.5-39.4%) and survival rates (median overall survival (OS), 9.2-21.3 months). Moreover, anti-PD-1/PD-L1 yielded better outcomes when given as first-line therapy, and overexpression of PD-L1 in tumors showed better therapeutic effects. On the other hands, safety profiles were similar across agents and generally acceptable, with grade ≥3 treatment-related adverse effects (AEs) ranging from 9.5% to 15.6% and no new AEs were experienced by TNBC patients. Most grade ≥3 AEs are immune-mediated, which are manifested as neutropenia, fatigue, peripheral neuropathy, and anemia. PD-1/PD-L1 inhibitors showed promising efficacy and tolerable AEs, and thus may benefit TNBC patients. Further studies of randomized controlled trials with larger populations are needed to better confirm the potential of these agents.